Effects of organo-mineral fertilizers containing struvite from liquid digestate on the growth of baby-leaf lettuce and radish - Burato, Andrea; Džomba, Emir; Čengić-Džomba, Senada; Chrysargyris, Antonios; Kallikazarou, Nomiki; Melito, Sara; Marceddu, Daniele; González-Ángel, Sara; Giannini, Vittoria; Antoniou, Maria G.; Tzortzakis, Nikos G.; Boscaiu, Monica; et al. (My University, 2025)
Phosphorus (P) is crucial for plant growth, but its deficiency or low availability in soils often limits crop yield. To mitigate this issue, excessive amounts of mineral P fertilizers are commonly applied in intensive cropping systems causing environmental problems. Sustainable fertilizer production may be achieved by recovering waste as sources of nutrients, among which struvite (MgNH4PO4·6H2O) represents a promising candidate. However, its effectiveness in horticulture is under-researched. Herein, four different waste-derived organo-mineral fertilizers containing struvite, produced in four different countries (Bosnia and Herzegovina, Cyprus, Italy and Spain), were tested on baby leaf lettuce (Lactuca sativa L.) and radish (Raphanus sativus L.) grown under greenhouse conditions in each of the four countries. The experiments were laid out as a randomized block design with five treatments: growing medium without fertilizers (T1), growing medium enriched with traditional fertilizers at half and business as usual N-P-K rates (T2 and T3, respectively), and growing medium enriched with organo-mineral fertilizers containing struvite at half and business as usual N-P-K rates (T4 and T5, respectively). Fertilizers were applied only before sowing. Struvite-based fertilizers generally showed no phytotoxic effects on lettuce and radish seedlings. At harvest, unfertilized plants recorded the lowest yield both in lettuce and radish. Compared to traditional ones, struvite-based fertilizers had similar effects on crop height, leaf number, shoot and root biomass. Regardless of fertilizer type, increasing the dose from half to full rate did not always lead to proportional increases in crop growth, harvest index, agronomic efficiency and water productivity. These findings help determine the most effective waste sources for seedling production, laying the foundation for optimizing struvite characteristics.
Keywords: Crop yield; Nursery; Horticulture; Nutrient recycling; Phosphorus recovery; Waste-derived fertilizers; Waste streams